(untitled) (Bulletin KNOB, 2020)
In autumn 1953, at the invitation of the American Institute of Architects (AIA), Dutch architect Willem Dudok embarked on an almost three month-long lecture tour of over thirty universities in the United States of America. It was Dudok’s first experience of America. An analysis of the archival material of Dudok’s tour, never previously undertaken, offers starting points for a deeper consideration of Dudok’s reflections on his own career as architect and urban designer, and his view of architecture and urban design in the United States. Since his earliest housing projects in Hilversum around 1920, American architects had taken an interest in Dudok’s work, an interest that only increased after the completion of the Hilversum town hall in 1931. Although Dudok had received several invitations to lecture in America over the years, it only became a reality quite late in life. The programme laid out for him was an exceptionally busy one: in the course of eighty days he covered a large swathe of the eastern and central part of the United States. He lectured to architects, students and other interested parties, was invited to several receptions and dinners, and was taken on guided tours of many buildings and cities. He also stayed for a few days with Frank Lloyd Wright. Immediately upon arrival Dudok was impressed by the huge skyscrapers of Manhattan, although it was the engineering that made the greatest impression on him. He did not regard them as architecture for they lacked the ‘beauty of proportion and mutual harmony’. Dudok had prepared two lectures for his tour, largely based on a lecture he had already given in Brussels in 1950 for the Société Belge des Urbanistes et Architectes Modernistes. He argued for a spiritual value in architecture that would be reflected in the proper structural proportions. He felt that Americans had little idea of urban design as yet, and he made frequent mention of an ugliness and chaos similar to that in Asian cities. He favoured the development of garden cities, of which Hilversum was his great example, over close-set skyscrapers. In his view, a city’s beauty consisted above all of a well-judged alternation of repetition and variation in buildings. For his American audiences of students and young architects, Dudok’s lectures were probably their first encounter with his ideas and reflections on architecture and urban design. He illustrated his lectures with a large number of slides and impressed his audiences with the breadth of his oeuvre, which clearly consisted of much more than his world-famous town hall. After his visit, Dudok’s lectures were published in the Journal of the American Institute of Architects and eighteen months later he was awarded the AIA Gold Medal, the institute’s highest honour. Dudok is still the only Dutch architect to have received this accolade.